Tick morphology and pathogen-carrying potential in dogs from Bogor, Indonesia - HASANATUL KHUZAIMAH; USAMAH AFIFF; UPIK KESUMAWATI HADI; SUSI SOVIANA; SUPRIYONO SUPRIYONO (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Khuzaimah H, Afiff U, Hadi UK,  Soviana S, Supriyono. 2026. Tick morphology and pathogen-carrying potential in dogs from Bogor, Indonesia. Biodiversitas 27 (1): d270122. https://doi.org/10.13057/biodiv/d270122. Rhipicephalus sanguineus is a hard tick ectoparasite that usually infects dogs and acts as a potential vector for zoonotic pathogens such as Lyme disease, Ehrlichiosis, Babesiosis, and Rocky Mountain fever, which are commonly transmitted to humans and animals by ticks. This study aimed to detect pathogenic bacteria, such as Anaplasma spp., Rickettsia spp., and Borrelia spp., in ticks collected from dogs in Bogor. A total of 77 dogs were randomly examined from 217 dogs, and 142 ticks were collected from six dogs, with a prevalence rate of 7.29%. Tick identification showed that all ticks were R. sanguineus according to Anastos' identification key (1950). R. sanguineus has specific characteristics, such as spurs on its first coxae and hexagonal basis capitula. The tick samples were then extracted for DNA to detect pathogenic bacteria using polymerase chain reaction (PCR). The results based on the 17-kDa and gltA genes showed that one sample tested positive for Rickettsia sp., and the infection rate for Rickettsia spp. was 12/142 ticks (0.085%). This was closely related to Rickettsia felis, which was detected in an infested dog in Saint Kitts and Nevis. Based on the groEL gene, one positive Anaplasma sp. sample had an infection rate of 94/142 ticks (0.66%). It was closely related to Anaplasma platys, which was detected in China, based on the phylogenetic tree. Meanwhile, the flaB gene detection for Borrelia spp. yielded negative results in all tick samples, but related research has successfully detected Borrelia in R. sanguineus. These findings provide molecular evidence of R. sanguineus as a potential vector for Rickettsia and Anaplasma in Indonesia. Maintaining environmental hygiene and pet cleanliness is essential for tick control and the prevention of zoonotic transmission.